Penelitian yang sedang berkembang tentang Kewirausahaan di Perguruan Tinggi: Analisis Bibliometrik - Izzara, Widi Aliffa; Ganefri, Ganefri; Yulastri, Asmar (PAKAR Pendidikan, 2024)
Entrepreneurship in higher education has gained momentum as a significant research subject, especially in the last decade. New approaches to entrepreneurship education in universities recognize that the goal is not only to generate new businesses, but more broadly to develop students' critical thinking, problem-solving and innovation skills. In this competitive global economy, graduates with technical skills alone are not enough. It also requires the ability to innovate and adapt, and create new opportunities. In response, universities around the world have integrated entrepreneurship education into their curricula, seeking to equip graduates with a flexible and proactive mindset through various programs and initiatives. However, challenges in the implementation of entrepreneurship education include its effective integration into an often rigid and dense curriculum, as well as difficulties in measuring the long-term impact of entrepreneurship. This study aims to identify and visualize publications related to entrepreneurial learning in the context of higher education. Using bibliometric analysis with the main data source from the Scopus database, this study focused on publications between 2014 and 2023, resulting in 799 relevant documents to be further analyzed using Biblioshiny for data visualization. From the data filtering results, 265 publications were identified with an annual growth of 13.33% and 672 authors who have contributed to this field, signaling high interest from the research community. In-depth analysis revealed publication trends, the most prolific authors, the most active affiliations, and the most cited articles, providing a comprehensive picture of the current bibliometric landscape. These insights are important for educators, curriculum developers, and policymakers to inform the development of more effective educational programs and policies and highlight the need for further research on the impact of entrepreneurial learning and the integration of digital technologies in education. This research provides a foundation for future explorations into digital entrepreneurship, charting pathways for innovation and positive impact within the education sector